Water - Gravity - Gradient: A gathering in the floodplain of the Hout Bay valley - Seymour, Nicole (School of Architecture, Planning and Geomatics, 2017)
This dissertation departs with an enduring interest in matter. The research, in turn, becomes focused primarily on physicality and its implications for people. An empathetic attitude towards considering material developed as a founding precept for the design endeavour. The project can be described as a process which began by following water; the river, the land and the mediating edge. Water, viewed through the particular lens of this document, has an intelligence, an embedded and personified logic. This material logic is inescapably evident in the landscape with which I am most familiar, my home, the Hout Bay valley. This dissertation seeks to create an intervention which should encourage a new relationship with water in Hout Bay. It is through a gathering of found program; wood cutters, Zionist Christians, horse riders, joggers, walkers, bird watchers, gardeners and swimmers, that the community is brought together in the floodplain.